Endourologic strategies for a minimally invasive management of urinary tract stones in patients with urinary diversion - Zhong,FangLing (2018)
ABSTRACT Objective To present our experience in minimally invasive management of urinary tract stones in patients with urinary diversion. Materials and Methods We retrospectively reviewed 26 patients with urinary tract stones after cystectomy and urinary diversion. The types of urinary diversion were ileal conduit, colon conduit, ileal orthotopic neobladder in 19, 4, and 3 patients, respectively. At postoperative days 2, a plain KUB and urinary ultrasonography were performed in order to assess stone fragmentation or hydronephrosis. According to postoperative imaging, stone free rate (SFR) was defined as complete absence of fragments or residual stones less than 4mm. Results 19 patients were treated with minimally invasive percutaneous lithotripsy (MPCNL) and 2 patients required second-look MPCNL. Anterograde flexible ureteroscopy was performed in 2 patients, while in 2 patients a combined anterograde and retrograde approach was required. Three reservoir stones were treated by transurethral neo-bladder lithotripsy. Postoperative significant complications occurred in 2 patients (7.7%). The highest percentage of stone composition was struvite, as a result of chronic urinary tract infection (UTI). SFR was 88.5% (23 of 26). Conclusions Our experience showed that MPCNL is a safe and effective treatment modality with little morbidity for renal and upper ureteral stones in patients with urinary diversion. For middle and lower ureteral stones, an anterograde approach could be also considered as a first line treatment, but a combined anterograde and retrograde approach was required when the anterograde access alone cannot provide acceptable results.